Analysis of proinflammatory cytokine responses in Takayasu arteritis - Rabia Deniz,; Aysın Tulunay-Virlan,; Filiz Ture Ozdemir,; Ali Ugur Unal,; Gulsen Ozen,; Fatma Alibaz-Oner,; Imren Aydin-Tatli,; Haner Direskeneli, (Archives of Rheumatology, 2024)
Objectives: This study aimed to investigate the expression of proinflammatory cytokines under long-term T helper (Th) 17 cell inducing conditions in Takayasu arteritis (TAK), a granulomatous vasculitis with adaptive immune responses. Patients and methods: This cross-sectional study was conducted between May 2014 and April 2017. Peripheral blood mononuclear cells from 25 patients (23 females, 2 males; mean age: 42.7±15.5 years; range, 20 to 69 years) with TAK and 25 healthy controls (HCs; 11 females, 14 males; mean age: 39.1±9.3 years; range, 21 to 64 years) were cultured in Th17 cell-inducing conditions for six days. Cultured cells were stained with conjugated monoclonal antibodies to determine the intracellular cytokine secretion by flow cytometry. Supernatant samples were measured with sandwich enzyme-linked immunosorbent assay for interferon-gamma (IFN-γ), interleukin (IL)-17, IL-7, IL-21, and IL-22 levels. Results: Under Th17 cell-inducing conditions, IFN-γ secretion was significantly higher in the TAK group compared to HCs (p<0.005). Unstimulated serum cytokine levels showed no differences between the TAK and HC groups, except for IL-7. Both IL-17 and IFN-γ secretion showed significant increases in TAK and IL-17 secretion in HCs in comparison of unstimulated and stimulated samples for each individual (p values, 0.022, 0.005, and 0.016, respectively). The production of IL-17 and IFN-γ by CD4+ , CD8+ , and γδ+ T cells and B cells was not found to be significantly different between TAK patients and HCs. No differences were observed between the subgroups of TAK according to disease activity or treatment in IL-17 and IFN-γ production. Conclusion: This study supports cell-mediated cytotoxicity as the main pathogenetic mechanism of TAK. T cells express higher levels of IFN-γ in TAK but not IL-17. Supernatant analysis indicated significantly higher IFN-γ production, which significantly increased after induction, suggesting the contribution of different inflammatory cells (probably CD8+ and γδ+ T cells) to IFN-γ production in TAK.